ANALISIS PENERAPAN PRINSIP GOOD GOVERNANCE DALAM PENGENDALIAN ADMINISTRASI DI SEKRETARIAT DAERAH KOTA SERANG - Yunita, Yunita; Bangsawan, Try Adhi; Saepudin, Eli Apud (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
This study aims to examine how good governance values are applied in administrative control at the Serang City Regional Secretariat. The focus of the research includes the impact of implementation on efficiency and accountability, as well as supporting and inhibiting factors. Qualitative descriptive studies using interviews, observation, and documentation were used to collect data in this study. Mardiasmo's (2009) theory is used as the analytical framework, which emphasizes three main indicators of good governance: transparency, accountability, and efficiency and effectiveness. The results of this study also show that the principle of transparency has begun to be implemented through administrative information disclosure, although public access is still limited. Accountability has been realized in performance reporting, but it is not yet fully optimal due to incomplete and untimely reporting. Efficiency and effectiveness are hampered by limitations in human resources, budget, and information technology. The main supporting factors are leadership commitment and the availability of regulations, while obstacles include a work culture that is not yet accountable and weak internal supervision. This study recommends strengthening human resource capacity, digitizing administration, and improving an accountable work culture to realize a more orderly and transparent system of government.